'Rechtsstaat' and European criminal law – From the end of sovereignty. Issue 1 (March 2021) - Braum, Stefan
Whoever punishes is sovereign. Those who punish fairly – or legitimately – are sovereign. At least that is how it was yesterday. But is it still the case today? Sovereignty is not what it used to be. Neither are punishments. What is the result? We do not know. I will try to explain the change of sovereignty in criminal law through the draft Regulation on the collection of electronic evidence. I am going to discuss three axes to set the framework for a critique. - What we know - What changes - What we can hope for or fear.